Atitudes de design e inovação: um estudo de caso em uma organização mediatech - Hohmann, Luana Machado (Universidade do Vale do Rio dos Sinos, 2020)
Mediatech organizations are thus defined by combining media and technology in a digital way. These organizations represent a new paradigm in content distribution and, therefore, they need to continue advancing in proposing new business models to remain competitive. However, the skills and competences of designers are still little explored in the leadership of organizations. To this end, a case study of design attitudes and their influence on the innovation process in a mediatech organization was carried out. Data collection involved documentary research, direct observation and semi-structured interviews with the organization's design leaders. To analyze these data, content analysis and mapping of the innovation process was carried out during a hackathon event, which made it possible to identify the design attitudes present in the organization from the aspects of the design attitude model proposed by Michlewski (2008, 2015). The research addresses the practice of design in a mediatech organization and seeks to understand whether these aspects are present and which attitudes stand out most at the strategic level of the area of experience and innovation of the digital core of the organization.
Keywords: Design estratégico; Inovação; Design attitude; Strategic design; Innovation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial